2012
DOI: 10.1037/a0026846
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood context and adjustment in African American youths from single mother homes: The intervening role of hopelessness.

Abstract: African American youths from single mother homes are more likely to live in neighborhoods characterized by greater risk and fewer resources than youth from two parent homes or European American youths; in turn, such adverse conditions are associated with increased adjustment problems. Despite this well-established vulnerability, relatively little is known about variables linking neighborhood context to youth adjustment. With the aim of identifying a potential youth-focused intervening variable amenable to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Studies suggest that this pattern may emerge as a consequence of the lack of opportunities for young adults in disadvantaged communities to pursue goals and the absence of role models who exemplify and support the pursuit of conventional life goals (Fuligni & Hardway, ). Disadvantaged communities in general provide minimal resources to help young adults embark on constructive life paths and to promote feelings of hopelessness about the future (Cutrona, Russell, Hessling, Brown, & Murry, ; Gonzalez et al., ). For young African American men with unstable social lives, disadvantaged community environments may take a uniquely powerful toll on their ability to set and pursue goals for the future, rendering substance use an attractive alternative (Paschall et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that this pattern may emerge as a consequence of the lack of opportunities for young adults in disadvantaged communities to pursue goals and the absence of role models who exemplify and support the pursuit of conventional life goals (Fuligni & Hardway, ). Disadvantaged communities in general provide minimal resources to help young adults embark on constructive life paths and to promote feelings of hopelessness about the future (Cutrona, Russell, Hessling, Brown, & Murry, ; Gonzalez et al., ). For young African American men with unstable social lives, disadvantaged community environments may take a uniquely powerful toll on their ability to set and pursue goals for the future, rendering substance use an attractive alternative (Paschall et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For young men with little or no access to meaningful work and few social supports for pursuing their goals, the lack of resources in their community is expected to further undermine the likelihood they will set goals and pursue them. For young men struggling with unemployment and economic distress, residence in a challenging community is also expected to affect substance use by discouraging a future orientation (Gonzalez, Jones, Kincaid, & Cuellar, ; Paschall et al., ).…”
Section: Moderators Of the Pathways Between Harsh Parenting And Substmentioning
confidence: 99%
“…In their research, Gonzalez, Jones, Kincaid, and Cuellar () identified hopelessness and other detrimental childhood outcomes that may result from single‐mother parenting, especially within African American youth from low socioeconomic communities. Their finding that the mothers' perception of danger or risk within the neighborhood was linked to youth maladjustment was certainly germane.…”
Section: Discussionmentioning
confidence: 99%
“…Based on U.S. research, youth residing in risky neighborhoods exhibit adverse adjustment outcomes, including worse physical health (Esteban-Cornejo et al, 2016), decreased school self-efficacy and academic achievement (Galster, Santiago, Stack, & Cutsinger, 2016), more internalizing symptoms (Gonzalez, Jones, Kincaid, & Cuellar, 2012), and more externalizing behaviors (Jocson & McLoyd, 2015). For example, in a sample of African American single mothers and their adolescent children, mothers who perceived their neighborhoods as having a low sense of community and high crime rates had children who reported high levels of hopelessness and externalizing behaviors (Gonzalez et al, 2012).…”
Section: Neighborhood Research In the United Statesmentioning
confidence: 99%